Immunomodulation by splenectomy or by FTY720 protects the heart against ischemia reperfusion injury. (November 2015) - Goltz, D; Huss, S; Ramadori, E; Büttner, R; Diehl, L; Meyer, R
Summary The pathogenesis of myocardial ischemia‐reperfusion injury (MI/R) involves an inflammatory response in the myocardium undergoing reperfusion. Modulation of this response by splenectomy constitutes an option to protect the heart from MI/R. To mimic the effect of splenectomy in a pharmacological approach, the sphingosine‐1‐phosphate agonist FTY720 was applied at the onset of reperfusion. In a closed chest model of MI/R, infarct size was assessed by triphenyltetrazolium chloride staining after 1 h of ischemia and 24 h of reperfusion, and by Masson trichrome staining 21 days after reperfusion in splenectomised mice, mice post‐conditioned with FTY720 IP (1 mg/kg), and controls. In addition, hemodynamic parameters were recorded after 24 h and 21 days by catheterization. Infarct size, and immune cell invasion of phagocytic monocytes investigated by FACS after 24 h of reperfusion were significantly reduced by both splenectomy, and FTY720 treatment. Evaluation after 21 days of reperfusion revealed that FTY720 treated animals had an improved hemodynamic outcome compared to placebo treated as well as splenectomised animals. FTY720 treatment reduced cell injury as effectively as splenectomy by lowering the number of phagocytic monocytes invading the myocardium and ameliorated hemodynamic outcome within the first 21 days.